2019
DOI: 10.1038/s41467-019-11173-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analyses of hepatitis B virus X protein BH3-like domain and Bcl-xL interaction

Abstract: Hepatitis B virus (HBV) X protein, HBx, interacts with anti-apoptotic Bcl-2 and Bcl-xL proteins through its BH3-like motif to promote HBV replication and cytotoxicity. Here we report the crystal structure of HBx BH3-like motif in complex with Bcl-xL where the BH3-like motif adopts a short α-helix to snuggle into a hydrophobic pocket in Bcl-xL via its noncanonical Trp120 residue and conserved Leu123 residue. This binding pocket is ~2 Å away from the canonical BH3-only binding pocket in structures of Bcl-xL with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 44 publications
5
40
0
Order By: Relevance
“…Perhaps the most likely mechanism of the mediation of HBV transcription is that the interaction between the preS1 region of the large S protein and TIMM29 at mitochondria generates a signal to modulate HBV transcription, since a recent report showed that the HBV X protein and a mitochondria factor interacted and affected HBV gene expression via an unknown mechanism. 34 As such, the interaction of viral factors with mitochondrial components could be very attractive and important to do something in the course of viral infection. Although the mechanism would be very complicated, a higher expression of TIMM29 in HBV-infected cells might increase the TIMM29-preS1 interaction and vice versa, and thus the interaction should negatively signal to HBV transcription by recruiting large S protein expressed in the HBV-infected cells to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most likely mechanism of the mediation of HBV transcription is that the interaction between the preS1 region of the large S protein and TIMM29 at mitochondria generates a signal to modulate HBV transcription, since a recent report showed that the HBV X protein and a mitochondria factor interacted and affected HBV gene expression via an unknown mechanism. 34 As such, the interaction of viral factors with mitochondrial components could be very attractive and important to do something in the course of viral infection. Although the mechanism would be very complicated, a higher expression of TIMM29 in HBV-infected cells might increase the TIMM29-preS1 interaction and vice versa, and thus the interaction should negatively signal to HBV transcription by recruiting large S protein expressed in the HBV-infected cells to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] In the case of HBV, HBx as above and HBV polymerase were reported to be present in the mitochondria. 34,[40][41][42][43][44][45][46][47][48][49][50][51] Interaction between mitochondrial and viral factors in the mitochondria might be important for cancer formation. 52 After HBV infects hepatocytes, relaxed circular DNA (rcDNA) goes to the nucleus, where it is converted to covalently closed circular DNA (cccDNA).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the vast majority of virus-encoded apoptosis regulatory Bcl-2 proteins act by utilizing the canonical ligand-binding groove to sequester proapoptotic Bcl-2 family members, it has become apparent that this is not the sole mechanism utilized. In addition to binding proapoptotic proteins, viruses may target host prosurvival Bcl-2 proteins through the BH3-binding groove in a manner similar to but not identical to a BH3 motif, and Hepatitis B virus X protein was shown to engage the groove of Bcl-x L allowing viral replication to proceed [113].…”
Section: Virus-encoded Bcl-2 Homologsmentioning
confidence: 99%
“…Additionally, this interaction increases the rate of cell death [ 45 ]. This interaction is through a B-cell homology domain-3 like (BH3) structural motif found on HBx, whose structure was recently more clarified [ 46 ].…”
Section: Risk Factors and Risk Stratification For Hccmentioning
confidence: 99%